Differences in food and nutrient intakes between Australian‐ and Asian‐born women living in Australia: Results from the Australian Longitudinal Study on Women's Health. Issue 2 (27th December 2017) - Liu, Huaqing; Hall, John J.; Xu, Xiaoyue; Mishra, Gita D.; Byles, Julie E.
Abstract : Aim: To determine differences in food and nutrient intakes between Australian‐ and Asian‐born women living in Australia. Methods: Data were obtained from the Australian Longitudinal Study on Women's Health, including 6461 women born in Australia or Asia who completed food frequency questionnaires in 2001 and 2013. Diet was assessed using the Dietary Questionnaire for Epidemiological Studies version 2. Longitudinal generalised estimating‐equation modelling was performed to determine the effect of country of birth and survey year on fruit and vegetable intake. Results: Asian‐born women ate more cereals, soybeans and fish but less vegetables, legumes, dairy, meat and meat products than Australian‐born women both in 2001 and in 2013. Asian‐born women ate less cereals, rice and noodles, meat and its products ( P < 0.05) in 2013 than in 2001. The earlier people came to Australia, the less their rice and noodle intake per day. However, the reverse was demonstrated regarding vegetable intake. Asian‐born women had a lower daily intake of fat, calcium, zinc, thiamin, riboflavin, folate and retinol compared with those born in Australia. Conclusions: Asian‐born women living in Australia show different food and nutrient intakes from Australian‐born women, although their diets tend to deviate from typical Asian characteristics and approach a Western diet.